Pterostilbene Enhances Cytotoxicity and Chemosensitivity in Human Pancreatic Cancer Cells - Yi-Hao Hsu; Sheng-Yi Chen; Sheng-Yang Wang; Jer-An Lin; Gow-Chin Yen (Biomolecules, 2020)
Gemcitabine (GEM) drug resistance causes high mortality rates and poor outcomes in pancreatic ductal adenocarcinoma (PDAC) patients. Receptor for advanced glycation end products (RAGE) involvement in the GEM resistance process has been demonstrated. Therefore, finding a safe and effective way to inhibit receptors for RAGE-initiated GEM resistance is urgent. Pterostilbene (PTE), a natural methoxylated analogue derived from resveratrol and found in grapes and blueberries, has diverse bioactivities, such as antioxidative, anti-inflammatory, and anticancer qualities. The overall research objective was to determine the potential of PTE to enhance tumor cytotoxicity and chemosensitivity in PDAC cells. Our results have demonstrated that PTE induced S-phase cell cycle arrest, apoptosis, and autophagic cell death and inhibited multidrug resistance protein 1 (MDR1) expression by downregulating RAGE/PI3K/Akt signaling in both MIA PaCa-2 and MIA PaCa-2 GEMR cells (GEM-resistant cells). Remarkably, convincing evidence was established by RAGE small interfering RNA transfection. Taken together, our study demonstrated that PTE promoted chemosensitivity by inhibiting cell proliferation and MDR1 expression via the RAGE/PI3K/Akt axis in PDAC cells. The observations in these experiments indicate that PTE may play a crucial role in MDR1 modulation for PDAC treatment.